Media Literacy and Democracy in Indonesia: Addressing the Challenges of Fake News and Political Misinformation (Indonesian Discourse on Communication, Democracy, and Political Movements, 2025)
The proliferation of fake news and political misinformation has emerged as a significant challenge to democratic processes in Indonesia, particularly in the context of rapid digital media expansion and increased online political engagement. While digital platforms enable broader participation, they also facilitate the spread of misleading information that undermines public trust and informed citizenship. This study aims to examine how media literacy initiatives in Indonesia address the challenges posed by fake news and political misinformation in order to promote critical and informed democratic engagement. Employing a qualitative research design, the study analyzes media literacy programs implemented by government institutions, civil society organizations, educational initiatives, and digital platforms through policy documents, training materials, and public campaign content. The findings indicate that effective media literacy initiatives emphasize critical thinking, source verification, and digital ethics, while adapting communication strategies to local socio-cultural contexts. These initiatives seek not only to reduce the circulation of misinformation but also to empower citizens to actively and responsibly participate in democratic discourse. However, the study also identifies limitations related to uneven program accessibility and the lack of systematic integration into formal civic education frameworks. The urgency of this research lies in the increasing vulnerability of Indonesia’s digital public sphere to misinformation and political manipulation. The study contributes to academic debates by positioning media literacy as a long-term democratic intervention rather than a reactive corrective mechanism. It concludes that strengthening collaborative, inclusive, and sustainable media literacy frameworks is essential for enhancing democratic resilience, and recommends closer cooperation among state actors, civil society, and educational institutions to support informed political participation in Indonesia.